Comparison of outcomes of peritoneal dialysis between patients after failed kidney transplant and transplant-naïve patients: a meta-analysis of observational studies. Issue 1 (25th April 2021) - Meng, Xiaohua; Wu, Weifei; Xu, Shuang; Cheng, Zhiqun
Abstract: Purpose: The influence of prior failed kidney transplants on outcomes of peritoneal dialysis (PD) is unclear. Thus, we conducted a systematic review and meta-analysis to compare the outcomes of patients initiating PD after a failed kidney transplant with those initiating PD without a prior history of kidney transplantation. Methods: We searched PubMed, Embase, CENTRAL, and Google Scholar databases from inception until 25 November 2020. Our meta-analysis considered the absolute number of events of mortality, technical failures, and patients with peritonitis, and we also pooled multi-variable adjusted hazard ratios (HR). Results: We included 12 retrospective studies. For absolute number of events, our analysis indicated no statistically significant difference in technique failure [RR, 1.14; 95% CI, 0.80–1.61; I 2 =52%; p  = 0.48], number of patients with peritonitis [RR, 1.13; 95% CI, 0.97–1.32; I 2 =5%; p  = 0.11] and mortality [RR, 1.00; 95% CI, 0.67–1.50; I 2 =63%; p  = 0.99] between the study groups. The pooled analysis of adjusted HRs indicated no statistically significant difference in the risk of technique failure [HR, 1.25; 95% CI, 0.88–1.78; I 2 =79%; p  = 0.22], peritonitis [HR, 1.04; 95% CI, 0.72–1.50; I 2 =76%; p  = 0.85] and mortality [HR, 1.24; 95% CI, 0.77–2.00; I 2 =66%; p  = 0.38] between the study groups. Conclusion: Patients with kidney transplant failure initiating PD do not have an increased risk of mortality, technique failure, or peritonitis as compared to transplant-naïve patients initiating PD. Further studies are needed to evaluate the impact of prior and ongoing immunosuppression on PD outcomes.